2008
DOI: 10.1002/cbic.200700542
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Switching Excimer Beacon Assays For Ribonuclease H Kinetic Study

Abstract: RNase H is a ribonuclease that degrades the RNA strand in a RNA-DNA hybrid to produce 3'-hydroxyl-and 5'-phosphateterminated products. It is a nonspecific endonuclease that catalyzes the cleavage of RNA through an endonucleolytic mechanism, [1] aided by an enzyme-bound divalent metal ion; however, DNA strands or unhybridized RNA strands are not degraded. The enzyme is involved in several important cellular processes including DNA replication, DNA repair, and transcription. [2] Members of the RNase H family ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…1) (16), however, demonstration of their formation in living cells remains elusive. To investigate whether TERRA RNA G-quadruplexes exist in living cells, we employed a light-switching pyrene probe that has been designed to employ the capability of pyrene to form fluorescent excited-state dimers (excimers) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The advantage of the distance dependence of excimer formation with pyrene can be used as a unique excimer signaling device for detecting G-quadruplex structure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) (16), however, demonstration of their formation in living cells remains elusive. To investigate whether TERRA RNA G-quadruplexes exist in living cells, we employed a light-switching pyrene probe that has been designed to employ the capability of pyrene to form fluorescent excited-state dimers (excimers) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The advantage of the distance dependence of excimer formation with pyrene can be used as a unique excimer signaling device for detecting G-quadruplex structure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these limitations are now being addressed by the development of fluorescence assays based on resonance energy transfer (FRET) or an excimer mechanism. [2,[15][16][17] Although promising, these techniques are compromised by the requirement for double-labeled oligonucleotide substrates, limited chemical stability, and interference by external nonspecific events. In addition, the possibility that the bulky fluorescent groups might interfere with the kinetic behavior of the catalysts is always a concern.…”
Section: Introductionmentioning
confidence: 99%
“…K M for RNase H has been reported to vary from 19 to 4.2 mm. [2,12,17,29] The variation is the result of a variety of assay conditions, substrates, and methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA with intrastrand and interstrand dimers mainly of pyrene and perylene exhibit strong excimer fluorescence [11][12][13][14][15] and can also be applied in molecular beacons. [16][17][18][19] However, the excitation of pyrene requires highenergy UV light, a circumstance that limits the bioanalytic and imaging applications significantly. Recently, we reported that the excitation of perylene bisimide pairs at 505 nm yields an excimer-type shift of the fluorescence by ca.…”
Section: Introductionmentioning
confidence: 99%